O sonho do petróleo e a serpente das águas cuiabanas: Lobato e o Minhocão (Polifonia, 1997)
ABSTRACT: This study consists, similarly to a concert, of multiple voices regarding nature and its forms in Mato Grosso: the topography, the Pantanal, the river. In the text, the voice of Monteiro Lobato dialogues with the voices of the people who live on the banks of Cuiabá river. In the dialogue, landscapes, dreams, prophecies, fears and myths are convergent.